2021
DOI: 10.1111/ajo.13304
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term durability of uterine artery embolisation for treatment of symptomatic adenomyosis

Abstract: Adenomyosis is a benign condition characterised by ectopic endometrial invasion of the underlying myometrium, resulting in hyperplasia and hypertrophy of this muscular layer of the uterus. 1-3 Clinically, adenomyosis may manifest as debilitating heavy menstrual bleeding (HMB), dysmenorrhoea, symptoms related to uterine enlargement, chronic pelvic pain and dyspareunia. 4,5 The prevalence of adenomyosis is not well established. Reported figures vary from 0.8%, identified based on database diagnostic coding 6 , t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Uterine artery embolization (UAE) has been proposed as a less invasive alternative to hysterectomy to treat adenomyosis. During this angiographic procedure, an embolic agent is injected into the uterine arteries to induce ischaemic infarction of adenomyotic foci [ 101 , 102 ]. In an extensive review by de Bruyn et al [ 101 ], it was showed that UAE improves clinical symptoms in 83% of patients, but great JZ thickness is associated with decreased effectiveness.…”
Section: Non-surgical Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uterine artery embolization (UAE) has been proposed as a less invasive alternative to hysterectomy to treat adenomyosis. During this angiographic procedure, an embolic agent is injected into the uterine arteries to induce ischaemic infarction of adenomyotic foci [ 101 , 102 ]. In an extensive review by de Bruyn et al [ 101 ], it was showed that UAE improves clinical symptoms in 83% of patients, but great JZ thickness is associated with decreased effectiveness.…”
Section: Non-surgical Alternativesmentioning
confidence: 99%
“…In a more recent study [ 102 ], women having undergone UAE for adenomyosis were contacted via SMS, email, or phone calls and invited to participate in the follow-up study on a voluntary basis. Improvement of symptoms was indeed observed in 80% of patients responding to the survey, but it should be stressed that recall bias may limit the accuracy of these findings.…”
Section: Non-surgical Alternativesmentioning
confidence: 99%
“…As one of the direct clinical outcome assessments [ 11 ], patient-reported outcome (PRO)-based symptom and QoL measures serve as reliable approaches for patients with UFs throughout the full course of diagnosis [ 12 ], treatment [ 13 ], and disease management [ 14 ]. Consequently, measuring UF-related symptoms and QoL status in a valid and reliable manner could support high-quality practice and comprehensive patient management for patients of diverse cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Uterine artery embolisation (UAE) is an established treatment option for symptomatic uterine fibroids in all locations [1][2][3][4][5][6][7][8][9][10] and has shown early success in adenomyosis [11,12]. UAE offers several advantages in comparison to surgical options (myomectomy or hysterectomy), including shorter average length of hospital stay, shorter recovery period, similar rates of symptomatic improvement, retention of the uterus, and no requirement for general anaesthesia [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%